A perfect number is a positive integer, the sum of whose factors(except the number itself) add upto the number.
Example: 28 = 14 + 7 + 4 + 2 + 1
There are about 48 known perfect numbers at the time of writing this article.But none of them are odd. Computers have checked upto 10^{300} but could never find one. So I tried my luck disproving their existence.I had a little experience proving this (pefect squares have odd number of factors). But rather than disproving their existence I ended up finding constraints on their existence.
Let x be a odd perfect number.
Then x can be denoted as x = p^a.q^b.r^c ..…. where p, q, r..... are prime factors.
Theorem 1: One and only one of the prime factors have an odd power i.e. only one of a, b, c.... is odd and all others are even.
Proof:
All the combination of factors of x can be denoted by varying the powers of the prime factors.
The sum of all the factors of x can then be written as
s = (p^0 + p^1 + p^2 + ....p^a)(q^0 + ..... q^b)(r^0 + ...… r^c).....
x = (p^0 + p^1 + p^2+...p^a)(q^0 + ... q^b)(r^0+...r^c)...-p^a.q^b.r^c....
x = (1 + p + p^2 + ....p^a)(1 + ..... q^b)(1 + ...… r^c)..... - x
2x = (1 + p + p^2 + ....p^a)(1 + ..... q^b)(1 + ...… r^c).....
The left side of the equation has a 2 multiplied by a odd number. So the right should have one and only one even multiple.
Prime number is a odd number. An odd number raised to any positive integer power is also odd (3x3=9).
This implies if a is odd then (1 + p + p^2 + ....p^a) is even. Thus all other terms are odd and q, r, ..... are even.
Theorem 2: The only odd power is of the form 4m+1 and the prime factor is of the form 4k+1 where m is a non negative integer and k a positive integer
Proof:
From the previous proof we have
2x = (1 + p + p^2 + ....p^a)(1 + ..... q^b)(1 + ...… r^c).....
2x = (1 + p + p^2 + ....p^a).odd
Since x is also an odd number (1 + p + p^2 + ....p^a) is only once divisible by 2 and should be of the form 2(2n+1) where n is a non negative integer.
2(2n+1) = (1 + p + p^2 + ....p^a)
2(2n+1) = \frac{p^{a+1}-1}{p-1}
2(2n+1) = \frac{(1+p-1)^{a+1}-1}{p-1}
2(2n+1) = \frac{\binom{a+1}{0}+\binom{a+1}{1}(p-1)+...+\binom{a+1}{a+1}(p-1)^{a+1}-1}{p-1}
2(2n+1) = \frac{(a+1)(p-1)+\binom{a+1}{2}(p-1)^2...+(p-1)^{a+1}}{p-1}
2(2n+1) = (a+1)+\binom{a+1}{2}(p-1)...+(p-1)^a
Since (p-1) is even all the terms in the right except the 1st and the 2nd has at least 2^2 as factor.
So for rhs to be of the form 2(2n+1)
(a+1)=2(2m+1) => a = 4m+1
and
(p-1)=4k => p=4k+1
To show the above statement true
rhs = 2(2m+1 + (2m+1)a(2k) + even)
= 2(1 + even)
= 2(2n+1)
= lhs
= lhs
Conclusion:
x=(4k+1)^{4m+1}.O^2
Where O is a odd positive integer, m a whole number and k a natural number.
Please comment for any clarification.
Update: This result though in a different form has already been found out by Euler.
No comments:
Post a Comment